Mutation Analysis of ASXL1 in Normal Karyotype Myelodysplastic Syndromes: Experience From Pakistan - Sumera Shaikh; Nida Anwar; Saba Shahid; Shamim Mushtaq; Naveena Fatima; Saima Siddiqui; Qammar Jammal (Cancer Reports)
ABSTRACT Background The challenges in advancing treatment modalities for myelodysplastic syndromes (MDS) may stem from an incomplete understanding of the disease's complex pathophysiology and lack of reliable prognostic molecular markers. Advanced genomic techniques have revolutionized disease prognosis and risk stratification, particularly for cases with a normal karyotype. Aim The present study aimed to analyze ASXL1 mutations in MDS exhibiting a normal karyotype. Methods and Results The study enrolled 41 MDS patients with normal karyotypes. Genomic DNA was extracted from peripheral blood samples, followed by Sanger sequencing. The Chi‐square and Mann–Whitney U tests were applied to assess the association of age and hemogram with the occurrence of mutations. Survival analysis was done via the Kaplan–Meier method. Statistical operations were performed employing the IBM SPSS Statistics version 24. The patients had a median age of 40 years comprising 28 (68.3%) males and 13 (31.7%) females. ASXL1 mutations were identified in 8 (19.5%), particularly stopgain single nucleotide variant (SNV) and frameshift insertion. The median total leucocyte count × 109/L and blast percentage among the patients with ASXL1 mutation were 3.9 and 4.5, respectively. A survival of 85 weeks was recorded for ASXL1‐mutated and nonmutated cases. The association of ASXL1 mutation status with age and studied hematological parameters was found nonsignificant. Conclusion ASXL1 mutation plays a pivotal role in MDS prognosis, warranting assessment at diagnosis for risk stratification and treatment decisions. Early identification of ASXL1 mutation, particularly in low‐risk patients or those with normal karyotype, is imminent to identify patients exhibiting unfavorable prognosis. Integrating molecular insights into existing risk assessment holds significance for improved clinical outcomes, reduction in disease progression, and ultimately the improved quality of life and should be identified early in the course of disease even in the developing world.